Sistem Inaportnet dalam Pengurusan Surat Persetujuan Berlayar di BPTD Kelas II Aceh pada Pelabuhan Penyeberangan Singkil - Andi Yaser Arafat; Lilis Lilis; Fadiyah Hani Sabila (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The importance of the Sailing Approval Letter (SPB) is specifically regulated in Law Number 17 of 2008 concerning Shipping. Despite existing regulations, maritime accidents caused by technical factors and human error are still common. Safety and security issues, along with all shipping activities, are the joint responsibility of the ship owner and relevant port authorities. Ships are a very effective and efficient mode of transportation. Therefore, the port service system, including the process of ship entry and departure, is a critical component of the infrastructure needed to accelerate the maritime transportation system. The issuance of the SPB is currently carried out through the Inaportnet System as a form of digital service transformation in the port sector, managed by BPTD Class II Aceh. This research aims to analyze the implementation of the Inaportnet system in the management of SPB issuance for ships at the Singkil Ferry Port. The research method used is descriptive qualitative, with data collection techniques carried out through observation and interviews. The results show that the implementation of the Inaportnet system at BPTD Class II Aceh is quite effective in accelerating the administrative process of issuing the SPB. However, several constraints were identified, particularly related to weather factors and the limited number of human resources who fully master the Inaportnet application, which can affect the overall smoothness and speed of the service.